Análise documental e análise diplomática: perspectivas de interlocução de procedimentos - Nascimento, Lúcia Maria Barbosa do [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The Documental Analysis, as an intrinsic process to the Information Organization in the Information Science domain, establishes theoretical-methodological parameters, of a descriptive nature, that make explicit the procedures of the analytical doing that lead to the identification of the document contents. Based on the assumption that this procedure has a technical support in the intersection of procedures with Diplomatics, the aim was to recover the genesis of the Diplomatic conception and to expose the disciplinary base of theoretical fundaments that establish its procedures for the analyses of the document form and content, as well as expose the intersection of procedures and also in which moment this can occur to contribute effectively to the analytical doing in the Librarianship area. The approach uses the exploratorytheoretical and descriptive-comparative analysis to expose the assumptions that are the basis of the intersection of procedures and how this is carried out. In order to make explicit the proposed auxiliary technique, the document book is used, by means of a comparative-analytical procedure. It was observed that the diplomatic procedure presents elements that make it possible to systematize the acting of the analyst through the description of the procedure intersection, what allowed highlighting the aiming in doing analysis before the structural systematization of the document characteristics. The result helps in the identification of concepts starting from the articulation elements of form-content that reveal the distinct statements of the book. Therefore, from the diplomatic conception of document analysis it is possible to insert in DA context the view of the analysis of document to text by using structural elements that make explicit and that contextualize the external and internal aspects of the document, by comparing the dimension of its content by means of the dimension of its form.

A Análise Documental, como processo intrínseco à Organização da Informação no domínio da Ciência da Informação, estabelece parâmetros teórico-metodológicos, de natureza descritiva, que explicitam os procedimentos do fazer analítico que levam à identificação de conceitos do documento. Partindo do pressuposto que este procedimento encontra respaldo de natureza técnica na intersecção de procedimentos com a Diplomática, buscou-se resgatar a gênese da concepção Diplomática clássica e expor a base disciplinar dos fundamentos teóricos que estabelecem seus procedimentos de análise da forma e do conteúdo do documento, bem como expor a intersecção de procedimentos e em que momento esta pode ocorrer, de modo a contribuir efetivamente com o fazer analítico da área de Biblioteconomia. A abordagem utiliza a análise teórica exploratória e descritivocomparativa para exposição dos pressupostos que fundamentam a intersecção de procedimentos e como esta se realiza. Para a explicitação da técnica auxiliar proposta, faz-se uso do documento livro, utilizando-se de procedimento comparativoanalítico. Observou-se que o procedimento diplomático apresenta elementos que possibilitam sistematizar o agir do analista por meio da descrição da intersecção de procedimentos, o que permitiu evidenciar o momento da objetivação no fazer análise diante da sistematização estrutural das características do documento. O resultado auxilia na identificação de conceitos a partir dos elementos de articulação da formaconteúdo que revelem os distintos enunciados do livro. Logo, da concepção diplomática de análise do documento torna-se possível inserir no contexto da AD a visão de análise do documento ao texto por meio de elementos estruturais que explicitam e contextualizam os aspectos externos e internos do documento, ao cotejar a dimensão de seu conteúdo por meio da dimensão da sua forma.
Keywords: Análise documentária; Documental analysis; Classic Diplomatics; Documental form and content